Speed Up Image Encryption by Using RSA Algorithm - Al-Kadei, Faten H. Mohammed Sediq; Mardan, Huda Abdalkaream; Minas, Nevart A. (International Conference on Advanced Computing and Communication Systems (Online), 2020)
Since the existing RSA Algorithm needs long key sizes, requires big memory spaces and also a long execution time, it seems necessary to make some changes or taking some necessary precautions during the implementation of RSA in order to provide maximum security level. In this paper, three experiments were developed in order to examine the execution time of the processes of encryption and decryption and comparing the results together to elicit the improved points and discussing them. Moreover, some programming techniques will be used in order to speed up the process of encryption or decryption. The results indicate that the execution time of encryption process was improved by 14% in experiment 3 by using some techniques to speed up the process, the decryption process was improved as well by 22%.